Tissue erosion with perianal warts in HIV infection. Issue 4 (August 1993) - Nathan, M; Beck, S
Abstract : A case of painful tissue erosion due to perianal warts is described with HIV infection. Such a development can be avoided by frequent and careful monitoring.